The impact of health claims and food deprivation levels on health risk perceptions of fast-food restaurants. (January 2016) - Cadario, Romain
Abstract: Objective and procedure: We examined the effect of health claims and food deprivation levels on the health risk perceptions of fast-food restaurants. Consistent with previous research, we used a within-subjects experimental design to manipulate the health claims of fast-food restaurants using real brands: Subway, expressing strong health claims vs. McDonald's, expressing weak health claims. Participants who did not have access to nutrition information were asked to estimate the health risk associated with food items that were slightly more caloric for Subway than McDonald's (640 kcal vs. 600 kcal). We collected data through a web survey with a sample consisting of 414 American adults. Based on the USDA Food Insufficiency Indicator, participants were classified into two categorical food deprivation levels: food sufficiency and food insufficiency. Results and conclusions: We find that risk perceptions for obesity, diabetes and cardiac illnesses are lower (higher) for the restaurant with stronger (lower) health claims, i.e., Subway (McDonald's). Moreover, we also find that food deprivation levels moderate this effect, such that health risk underestimation is aggravated for individuals who suffer from food insufficiency. More precisely, we find that food insufficient individuals are more responsive to health claims, such that they perceive less health risk than food sufficient individuals for the restaurant with stronger health claims (Subway). Exploring the underlying mechanism of the latter effect, we found that dietary involvement mediates the relationship between food deprivation levels and health risk perceptions for the restaurant with stronger health claims (Subway). These results provide an interdisciplinary contribution in consumer psychology and public health. Highlights: We examined the effect of strong vs. weak health claims and food deprivation levels on health risk perceptions. Health claims were measured using real brands: Subway (strong claims) vs. McDonald's (weak claims). Food deprivation level was measured with the USDA Food Insufficiency Indicator. Risk perceptions for obesity, diabetes and cardiac illnesses are lower for Subway vs. McDonald's. The health risk underestimation is aggravated for individuals who suffer from food insufficiency.